Rekomendasi peningkatan soft skill mahasiswa melalui analisis nilai akademik dan feedback dari perusahaan tempat magang - Nugroho, Vinsensius Herdani Agung; Purnama, Ignatius Luddy Indra (Universitas Atma Jaya Yogyakarta, 2024)
The industry's demand for skilled graduates from Diploma 3 programs is currently assessed not only in terms of hard skills but also soft skills. The ability of skilled workers to manage projects, communicate effectively, and solve problems is a crucial aspect for obtaining promotions to permanent positions within companies. Currently, in the ABC study program at XYZ Academy, soft skills are often undervalued. They are primarily assessed based on student participation in organizations, which differs significantly from the soft skills sought by the industry. This gap motivates this research to analyze the relationship between students' academic performance and feedback from companies where they intern. The study explores academic data from Semesters 1 to 5 and company feedback over the past two years regarding interns. The analysis methods include descriptive analysis, clustering, text mining, correlation analysis, and regression modeling to identify factors influencing soft skill competencies. The findings reveal several issues, such as imbalances in courses related to hard and soft skills, with 33 out of 61 students (54%) receiving poor internship evaluations and company feedback indicating the need for better preparedness in the future. Therefore, the recommended actions to enhance students' soft skills include: transforming practical courses into collaborative projects, implementing a mentoring program with industry partners prior to internships, and improving teaching quality through workshops for educators with professional practitioners